Attitudes of Educational Qualification Diploma Students Towards Program of Designing E-Tests (WQC) A Field Study in The Faculty of Education at Tishreen University - Harba, Ali (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This study aimed at specifying attitudes of educational qualification diploma students towards program WonderShare Quiz Creator (WQC). This program is used for designing E-Tests. For this purpose, a valid an reliable scale of attitudes towards (WQC) was prepared by the researcher. The sample was selected randomly from Students of educational qualification diploma in the Faculty of Education at Tishreen University in academic year (2015-2016). The descriptive approach was used, so the scale of attitudes towards (WQC) was distributed to (126) students. The results of study showed:  The students of educational qualification diploma have a positive attitudes towards program (WQC), especially in attitude towards use of (WQC); (88.0%9) of students participating in this research enjoy designing e-tests by using of (WQC).  There is no statistical difference between students` scores mean due to gender variable (males and females) in every axis of the scale of attitudes towards (WQC). This means that both males and females of students have similar positive attitudes towards (WQC).  There are statistical differences among students` scores means due to specialization in bachelor variable (Scientific – Literature - Educational) in every axis of the scale of attitudes towards (WQC). This means that students` attitudes towards (WQC) are affected by specialization variable.  Many suggestions were introduced in light of results; the most important suggestion is to refresh courses of instructional Technology continuously.